Guaratiba verde: subsídios para o projeto de uma infra-estrutura verde em área de expansão urbana na cidade do Rio de Janeiro - Herzog, Cecilia Polacow (2009)
Discuss the possibilities in planning a sustainable urban basin drainage occupation, in order to achieve multifunctional goals: abiotic, biotic and cultural. The case study comprehends a hydrographic system on the west zone of the Rio de Janeiro's city. It has irreplaceable environmental and cultural potentialities that are being threatened due to the imminent urban expansion. The theoretical basis presents several topics related to ecological landscape planning. It starts with a brief history of its origins in the late XIX century, delineates its development during the XX century and emphasizes its substantive role in the sustainable development awareness during the last decades. It also supports effective inhabitant's participation during the entire process. The area was characterized to better understand its complexity and its ecological, cultural and economic opportunities. The drainage basin has significant natural ecosystems fragments that supply irreplaceable ecological services. This is an inter and transdisciplinary research. The assessment started searching for available data in both public and academic institutions, site trips and photographic documentation during a period of over three years. The area was mapped in several aspects, such as land use and vegetation cover, topography, flood and land slide vulnerable areas among others. The result was a geobiophysical analysis and diagnosis. Sacio-cultural issues addressed dwellers participation formally and informally. Cultural landscape reading and analysis of people's experiences were obtained through in-depth individual and group interviews. Environmental and cultural readings, analysis and diagnosis led to a green infrastructure proposal in two scales: drainage basin and neighborhood. Landscape ecology principies were applied to conserve or mitigate landscape pattern and processes.